2016
DOI: 10.3139/146.111388
|View full text |Cite
|
Sign up to set email alerts
|

Comparing predictions from constitutive equations and artificial neural network model of compressive behavior in carbon nanotube–aluminum reinforced ZA27 composites

Abstract: Hybrid carbon nanotube–aluminum reinforced ZA27 composites under hot compressive forces were investigated in the temperature range of 473 – 523 K with strain rates of 0.01 – 10 s−1. From the experimental data, the flow stress curves for increasing strain exhibit typical flow behavior associated with dynamic recrystallization softening. A comparison of predictions from an artificial neural network model and the constitutive equations to describe the hot compressive behavior was performed. Relative errors varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…Liu et al [133] compared the predictive accuracy of the traditional Arrhenius constitutive model and the ANN model for the deformation behavior of (CNT s -Al)/ZA27 composites under high temperature. It is found that because the traditional Arrhenius equation can only describe stable flow processes, such as strain hardening, the DRV and DRX of material, there is a large difference between the prediction results and the experiment when unstable deformations such as micro-cracks and shear bands occur.…”
Section: Artificial Neural Network Constitutive Modelmentioning
confidence: 99%
“…Liu et al [133] compared the predictive accuracy of the traditional Arrhenius constitutive model and the ANN model for the deformation behavior of (CNT s -Al)/ZA27 composites under high temperature. It is found that because the traditional Arrhenius equation can only describe stable flow processes, such as strain hardening, the DRV and DRX of material, there is a large difference between the prediction results and the experiment when unstable deformations such as micro-cracks and shear bands occur.…”
Section: Artificial Neural Network Constitutive Modelmentioning
confidence: 99%